Pemanfaatan Aplikasi GoodNovel dalam Peningkatan Apresiasi Sastra dan Literasi Digital Siswa SMK Paskita Global - Latiah, Ummi; Prawono, Shella Wati; Prawono, Shelly Yuliani; Pitriyani, Dea; Wahyuningrum, Alfani Dwi; Megawati, Erna; Patturahman, Maman; Nugraha, Santi (Darma Cendekia, 2023)
Digital literacy writing literary novels through the GoodNovel application. GoodNovel is a global original fiction platform dedicated to producing the latest generation of "classic" novels and providing a free zone of imagination for users by harnessing the power of technology. The results of interviews and questionnaires conducted by the team regarding interest in writing literary works showed that 68% of students did not like writing literary works. Several problems are factors that cause students not to be interested in writing literary works, namely lack of ideas in developing stories, lack of skill in writing novels, and not liking to write, this happens because students are less interested in reading and writing novels. The methods used in this activity are socialization, education, training and use of digital applications. The results of this activity were reviewed based on the output of the activity, namely an increase in interest in writing and digital literacy of Paskita Global Vocational School students. Thus, it can be concluded that this program has achieved its objectives.